Pemanfaatan Limbah Tekstil: Kain Perca sebagai Material Utama untuk Produk Fashion Berkelanjutan - Ranti Octavia Panjaitan; Dearmando Novhero Damanik; Magdalena Pebriani br Sitepu; Fuji Mori Sirait; Ikhsan Maulana; M. Ridho Nawawi; Sutan Maulana (Journal on Education, 2024)
The fashion industry is one of the major contributors to textile waste and environmental pollution, with millions of tons of fabric wasted every year. This research aims to explore the innovative use of patchwork as an eco-friendly material in sustainable fashion products. Using a qualitative approach with a case study method, data was collected through interviews, observations, and focus group discussions (FGDs) among the community and fashion industry players on Jl. William Iskandar Ps. V, Kenangan Baru, Kec. Percut Sei Tuan, Deli Serdang Regency. The results showed that the community began to show interest in environmentally friendly fashion products, especially the younger generation who understand the importance of sustainability. In addition, the development of prototype products such as patchwork-based bags, clothing and accessories showed positive results in terms of comfort and attractiveness. However, the challenge of changing people's perception of patchwork and educating them on its benefits still needs to be overcome. Thus, utilizing patchwork as a raw material in the fashion industry can not only reduce textile waste, but also encourage public awareness about sustainability in fashion.